2019
DOI: 10.1111/iwj.13176
|View full text |Cite
|
Sign up to set email alerts
|

Does closed incision negative wound pressure therapy in non‐traumatic major lower‐extremity amputations improve survival rates?

Abstract: Closed incision negative pressure wound therapy (CINPWT) has been shown to be clinically effective compared with the traditional gauze dressing, reducing surgical site infections and wound complications. We evaluated the effect of CINPWT compared with gauze dressing on the need for revision surgery and survival after non‐traumatic major lower amputation. We included 309 patients undergoing 403 major lower amputations in a retrospective study from January 1, 2010 to November 23, 2017. A total of 139 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These papers were scanned, and any duplicates or topic-unrelated articles were excluded. After analyzing the eligibility criteria, three of the seven studies could be included in our quantitative analysis (2,11,12). There were three retrospective casecontrol studies containing a total of 457 patients.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers were scanned, and any duplicates or topic-unrelated articles were excluded. After analyzing the eligibility criteria, three of the seven studies could be included in our quantitative analysis (2,11,12). There were three retrospective casecontrol studies containing a total of 457 patients.…”
Section: Study Selectionmentioning
confidence: 99%
“…Lower extremity amputation bears a high risk for postsurgical wound infections (1). Multi-morbid patients with diabetes-induced peripheral arterial disease represent the main subjects of major lower limb amputations (2). A combination of impaired blood supply and hyperglycemic states further increases the risk of surgical-site infections (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that ciNPWT may be used to reduce wound healing deficits in patients following periprosthetic lower limb fractures (level IV) [13]. In another retrospective case-control study, 309 patients undergoing 403 major lower limb amputations for non-traumatic indications were analysed with a specific focus on the potential effect of ciNPWT on postoperative survival rates [14]. Most common indications for lower limb amputation were diabetes and chronic wounds.…”
Section: Trauma and Orthopaedicsmentioning
confidence: 99%
“…Furthermore, there was no significant difference between the two groups with regards to rate of revision surgery (12.2% vs. 15.9%; ciNPWT vs. control; p = 0.740). The authors concluded that ciNPWT does not improve survival probability in patients undergoing major lower limb amputation for non-traumatic indications (level IV) [14]. Zayan et al [15] published results of a retrospective case series including 4 patients with upper limb amputation and 21 patients with lower limb amputation.…”
Section: Trauma and Orthopaedicsmentioning
confidence: 99%
“…Wound healing is strictly regulated by cytokines and growth factors released at the wound site [8]. Regeneration is uncommon, although there are hopes of forming a similar structure with the parent tissue [9]. Healing results in functionality and structurally satisfactory but not identical results [10].…”
Section: Intrinsic and Extrinsic Wound Healing Processesmentioning
confidence: 99%